Curriculum and pedagogy in a changing world - Chakraborty, Anya; Mardones, Daniel Johnson; Waghid, Yusef; Tusiime, Michael; Le Grange, Lesley LL; Abdul Razak, Dzulkifli (UNESCO MGIEP, 2022)
This chapter explores the evolving nature of curriculum and pedagogy in a rapidly changing world. It argues that curriculum is not, and should not be, a clearly delineated concept that can be applied uniformly across different systems of education. Rather, it should be dynamic, evolving and contextual, representing specific historical and political forces and actors. To capture some of this contextual diversity, the chapter provides an evidence-informed assessment of current trends in the curriculum and pedagogy fields. It outlines the different histories and traditions of curriculum and pedagogy, noting how the many ways education has been conceived and practised leave ongoing legacies. Some of the trends and challenges confronting contemporary curriculum and pedagogy are outlined, including (neo)colonialism, economism and neoliberalism, technologization of learning and educational neuroscience. The chapter recommends some approaches to hybrid learning ecologies and the increased need for opening up spaces for emotions and ‘being’ in education.